(untitled) (Central Medical College Journal, 2025)
Background: Diabetic Retinopathy (DR) is one of the most prevalent micro vascular complications that occur in diabetes mellitus patients & it causes variety of lesion within the retina which leads to blindness. Duration of DM and increased HbA1c level has been identified as a cause of development of DR by previous studies. This current study aimed to determine the relationship of duration of DM & HbA1c with diabetic retinopathy. Objective: To evaluate the association between the duration of DM & HbA1c with retinopathy. Materials and methods: A cross-sectional study was conducted at BIRDEM general hospital from July 2021 to June 2022. According to the inclusion criteria, 100 subjects aged over 30 years were selected. After obtaining informed written consent from the study subjects a structured questionnaire was completed to collect data which includes personal identification, demographic history, drug history and history of duration of DM & other systemic diseases. Collected data were analyzed by using SPSS (20). Data was analyzed by parametric test (Independent student t test), Chi-Square Test. Results: The study showed a rising prevalence of DR with duration of DM. It was seen that when the duration of DM was 5 years the prevalence of DR was only 2% & when the duration was more than 10 years the prevalence of DR was 72%. HbA1c (%) was also significantly higher in diabetic retinopathy patients (12.40±3.01) comparing without diabetic retinopathy patients (8.74±2.73). Conclusion: In this study we found that the DR patients had significantly longer duration history of DM and significantly higher FBG, HbA1c level (p<0.001). Central Medical College Journal Vol 9 No 1 January 2025 Page: 7-11